PENGEMBANGAN SISTEM DIAGNOSIS KOGNITIF FISIKA ONLINE UNTUK SMP - Mindyarto, Budi Naini; Rusilowati, Ani; Kartono, Kartono; Sugiyanto, Sugiyanto (Jurnal Penelitian Pendidikan, 2011)
The need for this study stems from the accumulation of non-tuntasan learn physics due to the integration of assessment with learning in school. The formulation of the problem is how to develop an online assessment system for the diagnosis of cognitive junior physics using computerized adaptive testing (CAT) in order to facilitate the realization of assessment for learning in school? While the goal is to design and build a prototype system question bank and online cognitive diagnostic assessment using CAT for junior high school Physics. Development is done using the system development life cycle (SDLC) and a checklist to identify the data on compliance with specifications question bank, a prototype system assessment, cognitive diagnosis report, and revised prototype. Exploratory descriptive approach shows that with open source technologies potentially resulting product can be run on the network to the Internet or local computer networks in schools. Physics problem decomposed into components of problemsolving as measured by two 2-tier multiple choice items. Problems (testlet) packaged in modules that are presented to the user is adaptive to the user’s level of cognitive ability. Cognitive profile of qualitative and quantitative diagnosis of the resulting constructive learning process for improvement. Prototype results of this study can be accessed at: http://aku-bisa.com.